A Review of the Use of Simulation in Dental Education. Issue 1 (February 2015) - Perry, Suzanne; Bridges, Susan Margaret; Burrow, Michael Francis
<x xml:space="preserve">Abstract</x> Summary Statement In line with the advances in technology and communication, medical simulations are being developed to support the acquisition of requisite psychomotor skills before real-life clinical applications. This review article aimed to give a general overview of simulation in a cognate field, clinical dental education. Simulations in dentistry are not a new phenomenon; however, recent developments in virtual-reality technology using computer-generated medical simulations of 3-dimensional images or environments are providing more optimal practice conditions to smooth the transition from the traditional model-based simulation laboratory to the clinic. Evidence as to the positive aspects of virtual reality include increased effectiveness in comparison with traditional simulation teaching techniques, more efficient learning, objective and reproducible feedback, unlimited training hours, and enhanced cost-effectiveness for teaching establishments. Negative aspects have been indicated as initial setup costs, faculty training, and the lack of a variety of content and current educational simulation programs.